Prenatal diagnosis of thalassaemia major resulting from Lepore/ beta-thalassaemia genotype. Issue 6 (December 1981) - Furbetta, M; Angius, A; Falchi, A M; Tuveri, T; Tannoia,; Pertosa, A P; Cao, A
Abstract : Antenatal diagnosis was carried out in a pregnancy at risk for beta-thalassaemia major/intermedia, resulting from the Lepore/ beta-thalassaemia genotype, by globin chain synthesis analysis on fetal blood obtained by placentocentesis at 19 weeks' gestation. As there was no radioactive incorporation in the beta-region, the fetus was considered to be a Lepore/ beta-thalassaemia genetic compound and aborted on parental request. After abortion, cord blood analysis confirmed the absence of beta-chain radioactivity.